Alterações oftalmológicas em pacientes pediátricos com leucemia linfoblástica aguda - Mendonça, Cristiano de Queiroz (2018)
Introduction: Acute Lymphoblastic Leukemia (ALL) is a cancer commonly found among young people and responsible for 26% of childhood cancer cases. Today, up to 90% of such patients have an average survival rate of five-year free of the illness. Ocular manifestations (OM) arising from ALLs might be secondary to tumor-induced vascular anomalies or related to direct infiltration of the neoplastic cells into the eye and orbit, or to medications used in treatment such as chemotherapy and glucocorticoids (GC). Since this is an oncological disease with a high potential for cure, in young individuals with a high life expectancy, the identification of possible long-term ocular complications resulting from the treatment and correlation with predictive factors of relapse of the disease may support the design of an ophthalmological protocol for these patients cases. yet existent in scientific literature. Objective: To characterize OM in pediatric patients under treatment for ALL and to evaluate if they are associated with predictive risk factors for relapse, with protocols (1999 or 2009), gender and cerebrospinal fluid (CSF) infiltration Methods: A prospective cohort study was conducted in children and adolescents with ALL from January 2013 to December 2017, followed by a systematic review associating pediatric patients under treatment for ALL and ocular hypertension (OH), because OH is the most prevalent OM. The patients underwent ophthalmologic evaluations before starting treatment (D0), on the eighth day (D8), at the 28th day (D28), and at six months (D6 months). Ocular hypertension (OH) was considered in results above 21 mmHg. Measures of visual acuity (VA) <20/40 were considered visual loss (VL). Results: The results of the cohort involved 55 patients and 18 (32.7%) presented OM, been OH (20.0%), retinal hemorrhage (7.3%) and VL (7.3%) the most frequent finds. A strong association was found between patients with OM and those with a high risk of relapse (p=0.035, Cramer V=0.31) and who used the 1999 protocol (p=0.022, Cramer V=0.32). The risk of OM in patients from the 1999 protocol was 1,799 (CI=1,154-2,804), while in those at high risk of relapse it was 1,647 (CI=1,111-2,442). The results of the systematic review were limited to a total of four publications, two of individual case reports, one report of five patients and another prospective descriptive with twelve patients, with results varying from total ocular pressure control and VA preservation, to irreversible blindness. Conclusion: Patients with ALL have a high incidence of OM due to the treatment and the disease itself, and it may even be asymptomatic and evolve with VL. Patients submitted to the 1999 protocol and at high risk of relapse are more likely to present OM and these variables are strongly associated. OH is the most prevalent OM. Few studies have been found correlating children with ALL and OH. Due to the possibility of disparate results from silent OH without visual changes to irreversible blindness. Therefore, a protocol is proposed that contemplates systematic ophthalmological examination with the measurement of IOP immediately after diagnosis of ALL (D0) and subsequently at D8, D28 and D6months.